Analisis Pelaksanaan TPACK dalam Pembelajaran di Perguruan Tinggi dan Implikasinya terhadap Student Engagement: Studi Kasus di IAIQH Bagu - Siti Ria Farhaeni; Saparudin; Emawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the implementation of Technological Pedagogical Content Knowledge (TPACK) in learning in the Research Methodology course of the Islamic Education Study Program at the Qamarul Huda Islamic Institute (IAIQH) Bagu and analyze its implications for student engagement. This study uses a qualitative approach with a case study type. The research subjects consisted of lecturers teaching the Research Methodology course and sixth-semester C-grade Islamic Education Study Program students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña which includes data condensation, data presentation, as well as drawing conclusions and verification. Data validity was carried out through source triangulation and technical triangulation. The results of the study indicate that the implementation of TPACK in learning has been carried out through the integration of technological, pedagogical, and material mastery aspects in the learning process. The use of technology such as PowerPoint, LCD projectors, WhatsApp Groups, and the internet is combined with interactive learning strategies through discussions, questions and answers, and providing contextual examples. The implementation of TPACK has had positive implications for student engagement, as evidenced by increased behavioral, emotional, and cognitive engagement during the learning process. However, the learning process still faces challenges such as limited facilities, unstable internet connections, and students' difficulty understanding scientific terms and complex research materials.